Stakeholder Salience Revisited: Refining, Redefining, and Refueling an Underdeveloped Conceptual Tool - Neville, Benjamin A.; Bell, Simon J.; Whitwell, Gregory J. (2011)
This article revisits and further develops Mitchell et al.’s (Acad Manag Rev 22(4):853–886, 1997) theory of stakeholder identification and salience. Stakeholder salience holds considerable unrealized potential for understanding how organizations may best manage multiple stakeholder relationships. While the salience framework has been cited numerous times, attempts to develop it further have been relatively limited. We begin by reviewing the key contributions of other researchers. We then identify and seek to resolve three residual weaknesses in Mitchell et al.’s (1997) framework, thereby strengthening its foundations for further development. We argue, first, that urgency is not relevant for identifying stakeholders; second, that it is primarily the moral legitimacy of the stakeholder’s claim that applies to stakeholder salience; and last, that the salience of stakeholders will vary as the degrees of the attributes vary. These insights inform revised definitions of stakeholder salience and legitimacy, and necessitate a new theoretical underpinning for the role of legitimacy. Finally, we present an extensive agenda for future research with the objective of refueling research in stakeholder salience.
Keywords: Urgency; Power; stakeholder salience; stakeholder identification; Legitimacy